Behavioural biases in retail investing and legal drivers of tax compliance: A post-pandemic comparative study across OECD Nations - Tripathi, Abhishek; Kalhapure, Balasaheb; Bhattacharya, Tamal; Singireddy, Jeevani; Ghosh, Rahul Kumar (The International tax journal, 2026)
Retail investor behavior has undergone profound transformation in the post-pandemic period as waves of digital participation, market volatility, fiscal stimulus, and social-media–driven investment narratives interacted with deeply rooted behavioral biases, ultimately reshaping portfolio choices, risk-taking patterns, and compliance with tax regulations across OECD nations. This paper examines the comparative post-pandemic evolution of key behavioral biases overconfidence, disposition effect, herd instinct, mental accounting, present bias, and loss aversion and analyzes how these biases affect investment decisions and shape voluntary and enforced tax compliance behaviors within different legal and administrative architectures. Synthesizing behavioral finance theory, prospect theory, comparative tax law, and OECD compliance frameworks, the study proposes a dual-lens conceptual model linking cognitive distortions with legal, institutional, and enforcement drivers of compliance. It highlights how digitalized tax systems, nudge-based policy design, third-party information reporting, penalty elasticity, and trust in institutions interact with investor psychology during periods of economic uncertainty. The study finds that behavioral biases intensified during the pandemic’s liquidity surges and retail trading boom, while compliance outcomes were mediated by legal clarity, audit probability, and taxpayer–state trust differentials across OECD nations. The proposed model creates a foundation for future empirical validation of post-pandemic behavioral evolution in retail investing and tax compliance.